2014
DOI: 10.1136/bmjopen-2014-006380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cardiovascular health: the Healthy Life in Suriname (HELISUR) study. A protocol of a cross-sectional study

Abstract: IntroductionObesity, hypertension and diabetes are on a dramatic rise in low-income and middle-income countries, and this foretells an overwhelming increase in chronic disease burden from cardiovascular disease. Therefore, rapid action should be taken through preventive population-based programmes. However, in these regions, data on the population distribution of cardiovascular risk factors, and of intermediate and final end points for cardiovascular disease are scarce. The Healthy Life in Suriname (HELISUR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
6
1
Order By: Relevance
“…However, in Suriname, a multiethnic, middle-income country with high cardiovascular risk in the main population groups of Asian and African descent (Diemer et al, 2014), we found moderate health literacy levels. Improvement of health literacy might be a practical approach to better implement preventive strategies, and this deserves further exploration in resource-limited countries.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in Suriname, a multiethnic, middle-income country with high cardiovascular risk in the main population groups of Asian and African descent (Diemer et al, 2014), we found moderate health literacy levels. Improvement of health literacy might be a practical approach to better implement preventive strategies, and this deserves further exploration in resource-limited countries.…”
Section: Discussioncontrasting
confidence: 54%
“…This large cross‐sectional study, which included participants between February 2013 and July 2015, was designed to investigate CVD risk factors among different ethnic groups in Paramaribo, the capital of Suriname. A detailed description of the study is reported elsewhere . In brief, 1800 participants, aged 18‐70 years old, were randomly sampled through a household sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the study is reported elsewhere. 20 In brief, 1800 participants, aged 18-70 years old, were randomly sampled through a household sampling method. The General Bureau of Statistics divided the capital into 1200 Census enumeration areas, consisting of 100-150 households, and randomly selected 18 enumeration areas stratified by ancestry.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…A detailed description of the HELISUR study design and participant recruitment has been published previously [23]. In short, between February 2013 and July 2015 a total of 1800 randomly selected non-institutionalized individuals (18 to 70 years) living in the capital Paramaribo were contacted and interviewed at home by trained interviewers.…”
Section: Study Populationmentioning
confidence: 99%
“…As such, the Healthy LIfe in SURiname (HELISUR) study was designed to describe the prevalence of cardiovascular risk factors, intermediate endpoints, and Physical activity and obesity: ethnic differences? 5 cardiovascular diseases among the different ethnic groups living within the capital Paramaribo [23]. The current report uses data from the HELISUR project to describe the association between obesity prevalence and PA characteristics (domain, duration and intensity) among the total population and across the Asian-and African-Surinamese population living in Paramaribo.…”
Section: Introductionmentioning
confidence: 99%